Public Service Innovation Driven by Community Participation in Local Government Institutions - Norhalidah (Jurnal Ragam Pengabdian, 2026)
Public service innovation is a strategic issue in public sector management and local government business, especially in the midst of increasing demands for efficiency, responsiveness, and public value creation. However, most studies still position innovation as the result of internal policies of government organizations, while the role of community participation is often treated as a supporting factor, rather than a primary driver of innovation. This research aims to analyze how community participation functions as the main driver of public service innovation in local government institutions, by placing the interaction between public actors and the community as the core of the service value creation process. This research uses a qualitative approach with a case study design on the Banjarmasin City Government. Data was collected through in- depth interviews with 15 informants consisting of local government officials, community representatives, and public service users, and supported by analysis of policy documents and observation of service processes. The data were analyzed using thematic analysis to identify participation patterns, collaboration mechanisms, and forms of innovation produced. The results of the study show that community participation not only contributes to service improvement, but actively shapes the direction, design, and implementation of public service innovations through feedback mechanisms, community initiatives, and collaborative problem-solving. These findings show that public service innovation is co-productive and depends on the capacity of institutions to strategically manage community participation. This research makes a theoretical contribution by expanding the perspective of public business management through the affirmation of community participation as a source of innovation, as well as practical contributions for local governments in designing sustainable public service innovation models based on public values.